Determining Reference Spectra for Medical Diagnosis Using Clustering Methods - Pancerz, Krzysztof; Paja, Wiesław; Jakubczyk, Paweł (Procedia computer science, 2023)
In the paper, we describe the procedure of determining reference spectra for medical diagnosis. In our research, we have used various clustering methods to extract spectra of a group of healthy patients participating in the determination of the final reference spectra. The results presented in the paper can be used in further research concerning the development of diagnostic algorithms based on comparing the spectra of the subjects, suspected by a specific disease unit, with developed reference spectra of healthy people.